QUR’ANIC INTERPRETATION METHOD AND ITS IMPACT ON CONTEMPORARY INTERPRETATION - Lukmanul Hakim; Asrizal Asrizal; Afrizal Nur; Agustiar Agustiar (Jurnal Ushuluddin, 2018)
This research aims at studying the Qur’anic interpretation method and its impact on contemporary interpretation. This is based on the lack of studies on the interpretation of the contemporary Qur’an, like the method of interpreting the Qur’an, typology and so on. Here, the result has found many things that happen in the interpretation method starting from the development of the initial interpretation or the classical period to modern times. From various methods that have developed, there are essentially only four overviews of interpretation methods with their respective advantages and disadvantages. Such methods are inseparable from the scholars who have developed them. If viewed from the sources of interpretation, the interpretation methods are classified into five categories, (a) bil al-ma’tsur, (b) bil al-riwayah, (c) bil al-manqul, (d) bil ra’yi/bil al-dirayah/bil al ma’qul and (e) bil al-izdiwaj (combination). Further, if seen from the method of explanation, they are divided into descriptive method (al-bayani) and comparative method (al maqarin). Referring to the extent of explanation, they are categorized into global method (al-ijmali) and detailed method (al-ithnaby). Lastly, if seen from the target and scientific aspects that are interpreted systematically, they are classified into analytical method (al-tahliliy) and thematic method (al-mawdhu’iy)